Experimental and Finite Element Analysis of Laser Stitch Welded Structure / Mohd Azmi Yunus ...[et al.] - Yunus, Mohd Azmi; Aziz Shah, Mohamad Azam Shah; Abdul Rani, Muhamad Norhisham; Wan Iskandar Mirza, Wan Imaan Izhan; Kushairi, Sahril (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Nowadays, the application of laser stitch welding in automotive manufacture has dramatically increased due to its capability in producing lightweight joints. The dynamic characteristics of laser stitch welded joints are important to be analysed in order to understand the effect of the joint towards the noise, vibration and harshness (NVH) of the assembled structure. However, the accuracy of dynamic characteristics of the finite element model is differ from the experimental data due to the invalid assumptions of the input value of the model properties. Understandably, physical phenomenon of the laser stitch welded joint is complex and consist of many uncertainties in order to model in details. In this paper, a few joint connectors are investigated to represent laser stitch welded joints by using finite element modelling method. In this paper, a different type of element connectors such as rigid body element (RBE), shell element and solid element format are explored to represent laser stitch weld joints of a thin plate welded structure. The predicted results of different types of element connectors are then compared in term of natural frequencies and mode shapes with the experimental counterparts. The comparisons of results reveal that shell element has better capability to represent laser stitch welded joint in comparison with other element connectors.